Associação entre fatores psicossociais e duração da gestação na coorte pré-natal brisa - MACIEL, Monyk Neves de Alencar (2018)
INTRODUCTION: Early discontinuation of the gestational period causes serious harm to the child, their families and society. Premature Birth (PB) is the greatest prenatal health issue due to its high morbidity and mortality. Identify the conditions that favor the occurrence of PB is a global challenge. Psychosocial factors, such as violence during pregnancy, stress, depression, risk behavior and social support, have been identified as risk factors for PB. GOALS: The first article proposed to verify the validity of the Social questionnaire Medical Outcomes Study (MOS) and its multidimensional characteristics in a sample of pregnant women using confirmatory factor analysis. The second article had as goal to analyze the association between psychosocial factors and the duration of gestation, from a proposed model, based on structural equation modeling. METHOD: Cohort study in two Brazilian cities, São Luís–MA e Ribeirão Preto–SP. A study sample of pregnant women and their newborn babies was used. Data was collected from February of 2010. Data collection consisted of interviews, gynecological exams, dental evaluation, anthropometry, and a self reported survey. Women were interviewed both before and after giving birth. A total of 1447 women participated in the study in the city of São Luís and 1400 in Ribeirão Preto. RESULTS: The first paper identified that, in São Luís, the MOS scale with three dimensions obtained the best index values (RMSA=0.077, CFI=0.977, TLI=0.973, WRMR=1.694). The application of the same model in Ribeirão Preto did not replicate the same goodness of fit (RMSA=0.099, CFI=0.968, TLI=0.963, WRMR=2.015). The second paper demonstrated that the theoretical model is well adjusted. The factors that had an effect on gestational age were socioeconomic status (EP=-0.153; p=0.006), women’s age (EP=- 0.075; p=0.012), the number of prenatal care visits (EP=0.139; p<0.001), and previous premature births (EP=-0.451; p<0.001). CONCLUSION: Social support is a multidimensional construct of second order, which is constituted by a material, affective/interactive, and emotional/informational dimensions. After using the modification index, the MOS scale presented an acceptable fit in São Luís, but not in Ribeirão Preto. Factors associated with a lower gestational age were, higher socioeconomic status, older women, and previous history of PB . Pregnant women who performed a greater number of consultations during the prenatal care visits had an association with a higher gestational age. Knowledge of the risk factors associated with early childbirth helps to identify women in situations of vulnerability. Therefore, it allows the elaboration of preventive strategies for the PT as, orientation on the risks for the older pregnant women, more attention the women with history of previous PB and the importance of the adequate prenatal care.